Damage, Fracture, and Fatigue of Ceramic-Matrix Composites - Li, Longbiao (Springer Singapore, 2018)
This book focuses on the damage, fracture and fatigue of ceramic-matrix composites. It investigates tensile damage and fracture, fatigue hysteresis, and the properties of interfaces subjected to cyclic fatigue loading. Further, it predicts fatigue life at room and elevated temperatures using newly developed damage models and methods, and it analyzes and compares damage, fracture and fatigue behavior of different fiber performs: unidirectional, cross-ply, 2D and 2.5D woven. The developed models and methods can be used to predict the damage and lifetime of ceramic-matrix composites during applications on hot section components. Ceramic-matrix composites (CMCs) are high-temperature structural materials with the significant advantages of high specific strength, high specific modulus, high temperature resistance and good thermal stability, which play a crucial role in the development of high thrust weight ratio aero engines. The critical nature of the application of these advanced materials makes comprehensive characterization a necessity, and as such this book provides designers with essential information pertaining not only to the strength of the materials, but also to their fatigue and damage characteristics.